PENGARUH PENAMBAHAN HEAT EXCHANGER TERHADAP PERFORMA COLD STORAGE SETELAH RETROFIT REFRIGERAN R410A - Eky Novianarenti; Projek Priyonggo; George Endri K; Imaniah Sriwijayasih; Rikky Leonard; Arrad Ghani Safitra, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Cold Storage is a machine used to store a product at a certain temperature that can maintain the product so that it does not rot quickly. In the fluid machinery laboratory of the Surabaya State Polytechnic of Shipping, there is a Cold Storage that uses R410a as rettrofited refrigerant from R22. This test uses a cooling load in the form of water and vegetables. This system is designed to ensure an efficient cooling process by maintaining the temperature of the cooling room at an optimal level. The cooling system can work quite well and according to plan and the temperature of the cooling room can reach 4° C. The compressor calculation produces a performance of 0.054398 kW and decreased 2.5% than without LSHX. While the qcond increases to 0.34314 kW. It can be seen that the COP with a liquid suction heat exchanger with load inceases from 5.404 without LSHX to 5.501 with LSHX.